Impact of pharmacist-led interventions on influenza vaccination rates in high-risk populations - Gupta, Khushboo; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
Two pandemic outbreaks of H1N1 influenza have occurred in the past century: the Spanish flu in 1918 and the swine flu in 2009. It has been the most common human influenza virus subtype, causing a considerable amount of illness and mortality on a global scale. Antiviral prophylaxis is used in the event of unexpected influenza outbreaks to immediately stop the virus's spread. However, the effectiveness of antiviral medications in treating influenza appears questionable because drug-resistant strains are becoming more prevalent. Additionally, currently existing influenza vaccinations are strain-specific and need to be periodically reformulated to incorporate a combination of the strains of the influenza A and B viruses that are now in circulation. The development of a humoral immune response against the extremely changeable hemagglutinin protein is the issue with these vaccines. Furthermore, in the event of an unexpected epidemic, it is challenging to ensure their timely and sufficient availability. Therefore, the development of a more effective vaccine strategy that can provide universal or at least broad protection against the constantly evolving influenza virus strains in the global population is urgently needed.